The STRATEGI PERANCANGAN KEMASAN BARU HOME INDUSTRY LANS MOONCAKE - Limbang, Melinda Amanda; Dektisa, Andrian; Malkisedek, Mendy Hosana (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
Lan's Mooncake is a small and medium-sized business that has just arrived in the city of Surabaya. The packaging used by Lans Mooncake has not fully fulfilled the function of the packaging, causing difficulties for Lans Mooncake. Therefore, designing and designing new packaging for Lans Mooncake Surabaya is very important by making new attractive, suitable and effective packaging to maintain product quality, increase sales, attractiveness and competitiveness by exploring current trends and combining it with the cultural characteristics of Chinese people. The method used is qualitative through interviews, observation and literature so that the packaging designed is in accordance with the target market, target audience and owner of Lan's Mooncake.